Water Debt Indicator Reveals Where Agricultural Water Use Exceeds Sustainable Levels. Issue 3 (28th March 2019) - Tuninetti, Marta; Tamea, Stefania; Dalin, Carole
Abstract: Agriculture overexploits water resources in many regions, as water stress metrics highlight. Tracing back the causes of water overuses and separately accounting for soil water, surface water and groundwater resources is an open challenge to monitor the sustainability of agricultural water use. We introduce the "water debt repayment time" indicator, measuring the time required to replenish water resources used for annual crop production. This indicator disentangles source‐ and crop‐specific water overuses at a high spatial resolution. Globally, we find that wheat and rice production critically overuses groundwater resources and cotton production overuses both surface water and groundwater. Locally, unsustainable production is found over the Sabarmati Basin and in the Chao Phraya Basin, where the repayment time exceeds 5 years in many cultivated areas. Critical overuses are also found over the High Plain and Indo‐Gangetic Plains, where the repayment times reach 50 years. Unsustainable irrigation is often a consequence of growing crops during local dry seasons. Key Points: The water debt evaluates the time required for the hydrological cycle to renew the water used for annual crop production The water debt complements the water footprint indicator in sustainability assessments The water debt unpacks the spectrum of crop responsibilities behind unsustainable freshwater use